Rate modulation detection thresholds for cochlear implant users - Brochier, Tim; McKay, Colette; McDermott, Hugh (The Journal of the Acoustical Society of America, 2018)
The perception of temporal amplitude modulations is critical for speech understanding by cochlear implant (CI) users. The present study compared the ability of CI users to detect sinusoidal modulations of the electrical stimulation rate and current level, at different presentation levels (80% and 40% of the dynamic range) and modulation frequencies (10 and 100 Hz). Rate modulation detection thresholds (RMDTs) and amplitude modulation detection thresholds (AMDTs) were measured and compared to assess whether there was a perceptual advantage to either modulation method. Both RMDTs and AMDTs improved with increasing presentation level and decreasing modulation frequency. RMDTs and AMDTs were correlated, indicating that a common processing mechanism may underlie the perception of rate modulation and amplitude modulation, or that some subject-dependent factors affect both types of modulation detection.